Efficacy of regional anaesthesia for paediatric surgery: Experience from a surgical expedition - OM Fatungase; CC Nwokoro; EA Emmanuel; SO Akodu; RO Shoyemi; LO Amosu (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: In developing countries where resources are scarce and health care financing is essentially by out-of-pocket payment, a surgical expedition is often a huge economic relief. Children are a category of the vulnerable group that can benefit from such exercises. However, an anaesthesia technique that is economical in both human and material resources should be explored, Objective: To describe the outcome of regional anaesthesia techniques during a surgical expedition for paediatric patients. Methods: Children aged 6 months to 16 years, who had been previously screened for free surgery in different surgical specialities, were recruited for the study. Results: Fifty-six (56) children were screened but only 35 were recruited for the surgical expedition. There were nineteen (19) males and sixteen (16) females with a male to female ratio of 1.5:1. Surgical procedures covered surgical specialities such as orthopaedics, plastic and general paediatric surgery. All the patients had one form of regional technique and/or peripheral nerve blocks. There were no intra-operative or post-operative anaesthetic complications up to a period of 30-days while on follow-up care. Conclusion: Regional anaesthesia is safe and a cheap choice of anaesthesia in children during surgical expeditions.